Didactical Design for Overcoming Students' Learning Obstacles on the Inverse Function Concept - Muin, Abdul; Pratiwi, Arista Ambar; Satriawati, Gusni (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThe inverse function in secondary schools is still a difficult concept to learn. Meanwhile, in national exams or competitions this problem often arises. Didactic design is an attempt to improve the learning process. The purpose of this study is to identify the epistemological obstacle, to develop the learning designs, and to describe the students’ responses regarding the implementation of inverse function’s concept learning designs in the class. This research was held in one of Senior High School in South Tangerang of 38 people from class X. The research method is Didactical Design Research (DDR). This method is conducted from three stages, prospective analysis, metapedia didactic analysis, and retrospective analysis. The result of the study was indicated that the student’s obstacles are according to predictions and didactical design still generates some new epistemological obstacle. The revised didactical design was obtained by updating the initial didactical design to resolve the obstacle. The revised didactical design includes choosing vocabulary, adding new instructions, and expanding predictions and anticipating student responses.AbstrakFungsi invers di sekolah menengah masih merupakan konsep yang sulit dipelajari. Sedangkan dalam ujian atau kompetisi nasional masalah ini sering muncul. Desain didaktik merupakan upaya untuk meningkatkan proses pembelajaran. Tujuan penelitian ini adalah untuk mengidentifikasi hambatan epistemologis, mengembangkan desain pembelajaran, dan mendeskripsikan tanggapan siswa terkait penerapan desain pembelajaran konsep fungsi invers di kelas. Penelitian ini dilaksanakan di salah satu Sekolah Menengah Atas di Tangerang Selatan yang berjumlah 38 orang dari kelas X. Metode penelitian yang digunakan adalah Penelitian Desain Didaktik. Metode ini dilakukan dari tiga tahap yaitu analisis prospektif, analisis metapedadidaktik, dan analisis retrospektif. Hasil penelitian menunjukkan bahwa kesulitan yang dialami siswa sesuai dengan prediksi dan desain didaktis masih menimbulkan hambatan epistemologis baru. Desain didaktis yang direvisi diperoleh dengan memperbarui desain didaktis awal untuk menyelesaikan kesulitan. Desain didaktis yang direvisi terdiri atas: memilih kosakata, menambahkan instruksi baru, dan memperluas prediksi dan mengantisipasi respon siswa. How to Cite:  Muin, A., Pratiwi, A. A., Satriawati, G. (2020).  Didactical Design for Overcoming Students' Learning Obstacles on the Inverse Function Concept. TARBIYA: Journal of Education in Muslim Society, 7(2), 183-191. doi:10.15408/tjems.v7i2.13041.